Model Collaborative Governance Gugatan Ganti Rugi KUHAP dalam Mewujudkan Keadilan Korban Penipuan Jual Beli Online - Budi Herman; Alfitri Alfitri; Abdul Nadjib; Sriati Sriati (Journal of Education, Humaniora and Social Sciences (JEHSS), 2026)
The rapid growth of online buying and selling has increased the incidence of fraud, resulting in significant losses for victims. Although Articles 98–101 of the Indonesian Criminal Procedure Code (KUHAP) provide a legal mechanism for combining compensation claims with criminal proceedings, its implementation remains ineffective in practice. This study aims to analyze the implementation of collaborative governance in compensation claims under Articles 98–101 KUHAP and to develop a collaborative model oriented toward justice for victims of online transaction fraud. Employing a qualitative descriptive-analytical approach, the research was conducted at the Bengkulu High Prosecutor’s Office through in-depth interviews, observation, and document analysis. The findings reveal that compensation claims have not been treated as a collaborative process, as reflected in weak initial collaboration conditions, the absence of cross-institutional governance design, and informal, unsustained coordination among law enforcement agencies. This study proposes a collaborative governance model emphasizing strengthened initial conditions, collaborative institutional design, facilitative leadership of the prosecution service as a lead institution, and deliberative inter-agency processes. The proposed model is expected to integrate compensation claims more effectively into the criminal justice system and contribute to the realization of substantive justice for victims.